NA SAJI, NEW BALINESE KARAWITAN CREATION METHOD - I Wayan Diana Putra (Acintya, 2024)
Balinese karawitan composing basically uses intuition and accumulated artistic experience to create new karawitan music. The way the composer works is by transferring the musical abstraction stored in the brain memory to the musicians in an imitative way. In addition to having artistic experience, Balinese composers must also have the intellect to create Balinese musical works. The composer's intellect can then give rise to a new Balinese musical creation methodology as a refinement of the previous Balinese musical creation methodology. The refinement of Balinese musical creation methodology also aims to create a direction or projection of Balinese musical creation that is more educational than a performance. Refinement by developing the methodology of previous karawitan composers such as I Wayan Beratha, I Nyoman Windha and Pande Made Sukerta as objects of study and comparison. After reviewing and comparing the three stages of composers, it was deemed necessary to refine the stages of reading, discussion and writing. This resulted in the creation of a new musical methodology called Na Saji. Na Saji is a newly initiated methodology for creating Balinese karawitan music. The methodology of creating Balinese karawitan music is called Na Saji. The name of the Na Saji method is taken from the first letter of each stage, the letter ‘N’, which in Balinese script reads ‘Na’. While saji refers to the meaning of serving or presentation. So Na Saji is a method for presenting the stages of creating Balinese gamelan works. The five stages of the Na Saji method are: nyelehin (observing), nureksin ( analyzing), nyurat (writing), ngendingin (singing) and nabuhang (playing). The abstract should be in one paragraph.The font is Cambria, 10 pt, italic, and justify. Abstract is in 200-250 words, which is followed by 3-5 keywords.The abstract should succinctly describes your entire paper. It comprises of the purposes of the research, method, and the findings of the research, Novelty.